The Influence of the Competence of Auditors and Auditors Independence Could Affect the Integrity of the Financial Statements - Hasanuddin Hasanuddin (STIM LASHARAN JAYA MAKASSAR, 2017)
Integrities the underlying quality of the public trust and are a benchmark(benchmark) for the members in his decision to test all. This research aimed to analyze the effects of the competence of the auditors and the auditor independency on the integrity of the financial statements at the manufacturing company registered at Indonesia Stock Exchange. This research was conducted using the quantitative method on the financial statements of manufacturing company registered at Indonesia Stock Exchange from 2010-2013. The total sample comprised 24 companies which were determined using purposive sampling technique. The testing method of the hypotheses was the multiple regression analysis. The research results revealed that not all the variables were compatible with the hypotheses and all significant effects on the integrity of the financial statement.